Hot-pressed chromium doped zinc sulfide infrared transparent ceramics. (December 2016) - Li, Yiyu; Liu, Yin; Fedorov, Vladimir V.; Mirov, Sergey B.; Wu, Yiquan
Abstract: The present study, for the first time, reports the successful consolidation of chromium doped zinc sulfide (ZnS) polycrystalline infrared (IR) transparent ceramics (maximum transmittance of 67% at 11.6 μm) via hot pressing under vacuum. The phase composition of the as-sintered Cr 2+ :ZnS ceramics was determined to be primarily cubic ZnS sphalerite, with a minor amount of hexagonal ZnS wurtzite. Scanning electron microscopy (SEM) observation of the sintered ceramics showed a highly consolidated microstructure. IR absorption and photoluminescence measurements revealed that the Cr 2+ ions are tetrahedrally coordinated within the ZnS host lattice. Graphical abstract: